2022
DOI: 10.3389/fimmu.2022.828758
|View full text |Cite
|
Sign up to set email alerts
|

Flagella at the Host-Microbe Interface: Key Functions Intersect With Redundant Responses

Abstract: Many bacteria and other microbes achieve locomotion via flagella, which are organelles that function as a swimming motor. Depending on the environment, flagellar motility can serve a variety of beneficial functions and confer a fitness advantage. For example, within a mammalian host, flagellar motility can provide bacteria the ability to resist clearance by flow, facilitate access to host epithelial cells, and enable travel to nutrient niches. From the host’s perspective, the mobility that flagella impart to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 125 publications
(185 reference statements)
0
19
0
2
Order By: Relevance
“…It has been found that the pathogenesis of Campylobacter is closely related to the formation, adhesion, and invasion of the toxin of the flagella in the host epithelial cells [ 6 ]. The motility of the flagella helps the bacteria to cross the membrane of intestinal epithelial cells [ 7 ]. Therefore, the role of flagella in C. jejuni virulence should not be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the pathogenesis of Campylobacter is closely related to the formation, adhesion, and invasion of the toxin of the flagella in the host epithelial cells [ 6 ]. The motility of the flagella helps the bacteria to cross the membrane of intestinal epithelial cells [ 7 ]. Therefore, the role of flagella in C. jejuni virulence should not be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Many important human bacterial pathogens are highly motile (Lm, E. coli, P. aeruginosa ) 24,25 , yet few studies have assessed the impact of bacterial motility on infection 24,25,38 . Our study suggests that Lm motility enhances epithelial infection by allowing bacteria to efficiently scan the epithelium for target cells that are permissive to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Likely, using more detailed descriptions of the molecular sociology of the cell could further elucidate the link between genotype and cellular architecture for Prokaryotes and Archaea, as well as their environmental role. Chemotaxis has been shown to shape microbial ecosystems 25 and flagella are both a virulence factor and trigger immune homeostasis in gut microbiomes 26 .…”
Section: Discussionmentioning
confidence: 99%